Efeito do jejum no período ativo sobre as respostas metabólicas e inflamatórias em mulheres eutróficas e com obesidade - Wagner Alessandro dos Reis (2022)
Introduction: fasting has been used as a religious and medical practice for thousands of years and currently for weight loss, is related to the improvement of the metabolic and inflammatory profile in individuals with obesity. Objective: to investigate the effect of fasting during active periods on metabolic and inflammatory responses in adult eutrophic and women with obesity. Methods: women (18 to 59 years) were divided into the eutrophic group (BMI 18,5 to 24,9 kg/m2) and the obesity group (BMI ≥ 35,0 kg/m2). They were evaluated after a 10-hour overnight fasting and after a 10-hour active period of fasting. After night fasting they consumed a standardized breakfast. At the first moment, anthropometry, body composition, and resting energy expenditure (REE) were evaluated, and blood was drawn. In the second moment, a new blood sample was collected. For statistical analysis, a 5% significance level was adopted (p < 0.05). Results: 54 women participated in the study, 29 from the eutrophic group and 25 from the obesity group. After fasting in the active period, there was a reduction in insulin concentration and HOMA-IR and an increase in FFA and ketone body concentration in both eutrophic and obesity groups. As for the mediators of the inflammatory response, the concentration of CRP after fasting in the active period did not change in both groups but remained elevated in times 1 and 2 in the obesity group compared to the eutrophic group. There was a significant reduction of TNF-α only in the eutrophic group after fasting in the active period. At time 2, the concentration of TNF-α and MCP-1 was significantly higher in the obesity group. No changes were observed in the concentrations of IL-6, IL-10, and IL-18 after fasting in the active period in both groups. Considering time 2, there was a positive correlation between FFA with insulin, ketone bodies, and HOMA-IR in the eutrophic group and a positive correlation between FFA and glucose in the obesity group. In the eutrophic group, there was a positive correlation of IL-6 with glucose, TNF-α with IL-18 and MCP-1, IL-10 with IL-18, and of IL-18 with MCP-1, and a negative correlation of MCP-1 with FFA. In the obesity group, there were positive correlations between IL-6 and glucagon, IL-10 and glucagon, IL-18 and HOMA-IR, and negative correlations between MCP-1 and glucagon. Conclusion: the results of the present study showed that fasting during the active period affected glucose and lipid metabolism in both eutrophic and women with obesity and reduced the blood concentration of TNF-α in the eutrophic group. The concentrations of CRP, TNF-α and MCP-1 remained higher in the obesity group after the intervention. It is therefore observed that active-period fasting promoted changes in the metabolic and inflammatory profile of women with obesity differently from eutrophic women, and this difference may be related, in part, to the presence of IR and metabolic inflexibility in women with obesity.